Shock-wave hardening and spall fracture of austenitic steels under action of high-current nanosecond relativistic electron beam; Известия вузов. Физика; Т. 55, № 12-2 - Gnyusov S. F. Sergey Fedorovich; Rotshtein V. P.; Kitsanov S. A.; Mayer A. E.; Khishchenko K. V.; Levashov P. R. (2012, 2012)
Заглавие с экрана